Spartacus : an international magazine for gay men (Amsterdam: Spartacus)
"Fonds Suzan Daniel (FSD)Periodiciteit : onregelmatigRedactie : PO Box 3496, 1001 AG Amsterdamvanaf (1981) 2 : an international magazine for and about gay men"